ASSESSMENT OF EFFECTIVENESS OF SPORTS MASSAGE IN SUPPORTING OF WARM-UP - Boguszewski Dariusz; Kowalska Sylwia; Adamczyk Jakub Grzegorz; Białoszewski Dariusz (Kharkov National Pedagogical University, 2014)
Purpose: Warm-up is necessary part of sports training, because prepare the body for exercises and minimize the risk of injury. The aim of this study was assess the effectiveness of two types of warm-up: aerobic exercises and exercises with sports massage (before). Material and Methods: The research covered 59 women. All of them did fitness tests two times. Each test was preceded by a different form of warm-up (aerobic exercises, exercises with massage). For examined the differences t-Student test was used. Results : Warm-up with massage had positive effect for fitness level. More effective was exercises preceded by massage - differences in results (after the standard warm-up and warm-up with massage) in every tests were significant (p<0.001). Conclusion: Alternative form of warm-up can be effective way to preparing the body for exercises and make the training more attractive.